DEPENDENCE OF SEEDS GERMINATION OF HEMP INBRED LINES ON GENERATION AND DURATION OF STORAGE - Міщенко, С. В. (Scientific Progress & Innovations, 2013)
One of aspect of inbreeding (self-pollination) influence over proving of depression of signs of germinative energy and germination of seeds of modern hemp (Cannabis sativa L.) varieties is given in this article. It was proved, that germinative energy and germination is reduces due to increasing in the duration of storage of seeds. Germinative energy decreases during the self-pollination from I0 to I5. This regularity is typical for all investigated lines (samples). Substantial variation limits (h is from 1 to 68 and from 2 to 68) point to genotypic features of germinative energy and germination in the lines.